Kajian Pengenalan Gerakan Tangan Menggunakan Hidden Markov Model - Agus Mistiawan; Khairun Nisa; Dewy Yuliana; Hasby Rifky; Samsuryadi Samsuryadi (Annual Research Seminar (ARS), 2015)
In the recent few years, hand gesture recognition system received great attention to be researched because of its ability to create human computer interaction. In this paper a survey on recent research about hand gesture recognition is provided. A review of hand gesture and implementation of Hidden Markov Model (HMM) also highlighted.